Pengaruh Flash Sale dan Tagline “Gratis Ongkir” Shopee Terhadap Keputusan Pembelian Implusif Secara Online - Muhammad Iqbal Ferdiansyah (Postgraduate, University of Mataram, 2023)
This research was conducted to test the influence of Flash Sale and Tagline “Shopee Free Shipping on online Implusif purchase decisions. The population in this study was all Mataram Univesity students who used the Shopee application. The number of samples used in this study was 100 people using the survey method. The data collection techniques used are observation, questionnaires and online survey by distributing questionnaires through google forms. The data analysis tool used is the Hypotesis Test, which is a t test and f test using the SPSS 25 for windows program. The results of the analysis of the t test show that there is positive influence and significance. Flash Sale (X1) of the Implusive purchase decision (Y) with calculated value>ttable (4,765>1,984) and a significance level of 0,000<0,050. And the positive influence and significance of the Tagline “Free Shipping”(X2) on the decision of Implusive purchase (Y) with calculated value>ttable (6,231>1,984) and a significance level of 0,000<0,050